2016
DOI: 10.26637/mjm401/014
|View full text |Cite
|
Sign up to set email alerts
|

Two fluid axially symmetric cosmological models in f(R,T) theory of gravitation

Abstract: In this paper we have investigated two fluid axially symmetric cosmological models in $f(R, T)$ theory of gravitation. To get the deterministic model, we have assumed a supplementary condition $H_3=k H_1$, where $H_1$ and $H_3$ are Hubble parameters and $k$ is constant. Two-fluid model in $f(R, T)$ theory of gravitation, one fluid represents the matter content of the universe and another fluid is chosen to model the cosmic microwave background radiation. Some geometric aspects of the model are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Another investigation focused on two fluid axially symmetric cosmological models in the f (R, T ) theory of gravitation. By imposing a supplementary constraint H 3 = kH 1 , the authors [31] obtained a deterministic model that exhibited an expanding and shearing Universe. Some authors [32] presented a FRW cosmological model which satisfied the principle and considering the most recent research that suggested dark energy is responsible for the Universe's acceleration.…”
Section: Introductionmentioning
confidence: 99%
“…Another investigation focused on two fluid axially symmetric cosmological models in the f (R, T ) theory of gravitation. By imposing a supplementary constraint H 3 = kH 1 , the authors [31] obtained a deterministic model that exhibited an expanding and shearing Universe. Some authors [32] presented a FRW cosmological model which satisfied the principle and considering the most recent research that suggested dark energy is responsible for the Universe's acceleration.…”
Section: Introductionmentioning
confidence: 99%